EVALUASI PENGGUNAAN SITOSTATIKA PADA PASIEN KANKER SERVIKS DI INSTALASI RAWAT INAP - RATNA SARI DEWI (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2016)
Cervical cancer is one of the most common malignancies to women and it is still become a problem because of the increasing cervicalcancer patients. Cervical cancer is the most causing of death in women and generally the patients in advance stage already come to thehospital. the purpose of this research is to evaluate the used of cytostatics agent in cervical cancer patient. This research is an observationalresearch, data collected was used as retrospective by using patients medical record and analysed by using descriptive non-analytic method.Sample collected was taken by using purposive sampling method. The sample were then choose with particular criteria and only 86 patientsincluding the criteria. The evaluation of drug used in this research include right medicine, right indication, right patient and right dose.Result showed the presence of incorrect cases were incorrect doses, incorrect frequencies and incomplete data of 1.01%, 4.04%, 11.11%repectively.